The Growth of FHIA-17 Banana Seedlings with Application of Hijauan Paitan Fertilizer (Titonia diversifolia) and Cow Manure - Suswati Suswati; Asmah Indrawaty; Rizal Aziz; Eka Prasaditya Ramadhani (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Growth of FHIA-17 Banana Seedlings with the Application of Hijauan Paitan Fertilizer (Titonia Diversifolia) and Cow Manure. The aim of this study was to obtain data on the growth of FHIA-17 banana seedlings after application of T.diversifolia forage and cow manure. Using a factorial Randomized Block Design (CRD) with two treatment factors. The first factor is the forage dose of T. diversifolia (P) with 5 levels, P0=Control; P1=12.5 g kg-1 planting medium (equivalent to 5 tons ha-1); P2=25 g kg-1 planting medium (equivalent to 10 tons ha-1); P3=37.5 g / kg of planting media (equivalent to 15 tons ha-1); P4=50 g kg-1 of growing media (equivalent to 20 tons ha-1). The second factor is the dose of cow manure (K) with 5 treatment levels namely, K0=Control; P1=12.5 g kg-1 of growing media (equivalent to 5 tons ha-1); K2=25 g kg-1 of growing media (equivalent to 10 tons ha-1); K3= 37.5 g kg-1 of growing media (equivalent to 15 tons ha-1); K4=50 g kg-1 planting medium (equivalent to 20 tons ha-1 and repeated 2 (two) times. Observed parameters were plant height (cm), number of leaves, stem circumference (mm), plant wet weight (g), plant dry weight (g). The results of this study indicate that the application of forage T. diversifolia significantly affected plant height and number of leaves. It’s not real with respect to all observational parameters.